HIGHER EDUCATION IN THE REPUBLIC OF BULGARIA AT THE CROSSROAD - PROBLEMS AND MEASURES TO PREVENT THEM - Petrova, Desislava; Lazov, Lyubomir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This report identifies some of the problems of higher education in the Republic of Bulgaria related to the demographic crisis in the transition process and measures to overcome them. Emphasis is placed on the legislative framework, the rating system, the financing of higher education institutions and the science in them, the quality of training, the demand for staff from business and the supply of staff from universities, the admission of students and the offered forms of training. The analysis made by the authors is based on summarized data, which has been officially published, on the actual state of higher education in Bulgaria. Measures are proposed to overcome the problems, some of which are based on experience at the Technical University of Gabrovo.